Oxidative metabolism of polymorph nuclear leucocytes and cardiovascular metabolic syndrome development in males - L. A. Ruyatkina; Z. G. Bondareva; A. R. Antonov (Российский кардиологический журнал, 2005)
In 214 males with arterial hypertension (AH), divided into groups according to metabolic disorder quantity, and 45 healthy males, oxidative metabolism of polymorph nuclear leukocytes (OMPL) was assessed by chemiluminescent (CL) method. The possible association between parameters obtained and insulin-glucose parameters was investigated. Metabolic syndrome clustering was associated with non-linear OMPL progression. Stages of leukocyte functional status change were identified and described. Correlations between insulin-glucose parameters and CL indices varied according to metabolic disorders' severity in AH patients. The results support initial, pro-oxidant role of hyperinsulinemia, realized via OMPL increase at early stages of metabolic syndrome development in males.